High genetic diversity and population differentiation in Clarias gariepinus of Yala Swamp: Evidence from mitochondrial DNA sequences - Barasa, J.E.; Abila, R.; Grobler, J.P.; Agaba, Morris; Chemoiwa, E.J.; Kaunda-Arara, B. (Wiley, 2016)
In order to improve the conservation and sustainable utilization of the African catfish Clarias gariepinus of the Yala Swamp in Kenya, genetic diversity and population structure of Lakes Kanyaboli and Namboyo populations of the species were studied using DNA sequences of the mitochondrial D-loop control region. Genetic diversity inferred as haplotype and nucleotide diversities and number of singletons and shared haplotypes was higher in the Lake Kanyaboli population (LKG) than the Lake Namboyo population (LNG) of C. gariepinus. Thirty-one haplotypes were inferred, of which 25 (80·6%) were private or singletons, while only six (19·4%) haplotypes were shared between LKG and LNG. Both populations were differentiated, with FST value that was significantly different from zero (P < 0·05). Two clusters were inferred both from the maximum likelihood tree and the spanning networks of phylogenetic relationships of haplotypes. Mismatch distribution for total sample was multi-modal but individually, distributions were uni-modal in LKG, but multimodal in LNG. The mean ± s.d. raggedness index for both populations was 0·085 ± 0·098 and not significantly different from zero (P > 0·05). Individual raggedness indices were 0·015 and 0·154 for LKG and LNG respectively. Fu's Fs was negative for both populations, with LKG recording -14·871, while LNG had -2·565, significantly different from zero for LKG (P < 0·05), but the value for LNG was not significant (P > 0·05). Tajima's D was negative for both populations, with LKG recording -1·734, while LNG had -1·136. Standardized square differences (SSD) were 0·001 for LKG and 0·048 for LNG and non-significant between them (P > 0·05). Values between all populations were also not significantly different (P > 0·05), mean ± s.d. SSD 0·025 ± 0·033.